A study on the relationship between supervisor’s behavior and employee deviant behavior in Pejabat Daerah Ledang / Nisrin Raihan Zulkiffli - Zulkiffli, Nisrin Raihan (Faculty of Business and Management, 2015)
The research is being done with the purpose to study the relationship between supervisor’s behavior and employee deviant behavior in Pejabat Daerah Ledang. This study involved 32 respondents that consist from all departments in Pejabat Daerah Ledang. The data gathered and analyzed by using the Statistical Package for Social Science (SPSS) Version 20.0. The result from the study shows that both positive and negative supervisor’s behaviour does not have significant relationship with employee deviant behavior. Based on the findings, positive supervisor’s behavior and negative supervisor’s behavior has a weak relationship with employee deviant behavior.